Background Pollution's effect on AERMOD Air Quality Modeling - Reza Peykanpour Fard; Sohrab Hasheminejad; Maryam Ejei (اکولوژی انسانی, 2024)
Air pollution is the presence of harmful substances in the air at concentrations sufficient to cause adverse effects. This includes solid, liquid, or gaseous pollutants, as well as radioactive and non-radioactive radiation, present at levels and durations that compromise human and environmental health, or damage property and cultural heritage. This research aims to model the extent and spatial distribution of air pollution from the Zagros Economic Zone Mini Refinery in Islamabad Gharb County, Kermanshah Province, Iran. A secondary objective is to quantify the contribution of background pollution to the overall pollution levels and its interaction with emissions from the refinery. The AERMOD model, requiring surface and upper atmospheric meteorological data, was employed. Minimum surface data included wind speed and direction, dry-bulb temperature, and cloud cover. Results indicate a maximum 24-hour sulfur dioxide concentration of 192 µg/m³ without considering background pollution, increasing to approximately 200 µg/m³ when background levels are included. In both scenarios, concentrations remained below permissible limits, although background pollution contributed a 4% increase. The methodological improvements presented in this research are generally applicable and not limited to a specific time or location.